2017
DOI: 10.1186/s13073-017-0499-9
|View full text |Cite
|
Sign up to set email alerts
|

Methylation patterns in serum DNA for early identification of disseminated breast cancer

Abstract: BackgroundMonitoring treatment and early detection of fatal breast cancer (BC) remains a major unmet need. Aberrant circulating DNA methylation (DNAme) patterns are likely to provide a highly specific cancer signal. We hypothesized that cell-free DNAme markers could indicate disseminated breast cancer, even in the presence of substantial quantities of background DNA.MethodsWe used reduced representation bisulfite sequencing (RRBS) of 31 tissues and established serum assays based on ultra-high coverage bisulfit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Furthermore, cfDNA from cancer patients is known to carry tumour-specific changes in DNA methylation that are not present in the cfDNA of healthy donors [48,49]. Based on this, panels of tumour-specific methylated genes of potential value for early detection of BC have been described in cfDNA [50,51], including the RASSF1A, PITX2 [52,53] and EFC [54] genes, whose hypermethylation has been associated with poor prognosis of BC. Despite these promising findings, epigenetic alterations in cfDNA have not so far been explored in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cfDNA from cancer patients is known to carry tumour-specific changes in DNA methylation that are not present in the cfDNA of healthy donors [48,49]. Based on this, panels of tumour-specific methylated genes of potential value for early detection of BC have been described in cfDNA [50,51], including the RASSF1A, PITX2 [52,53] and EFC [54] genes, whose hypermethylation has been associated with poor prognosis of BC. Despite these promising findings, epigenetic alterations in cfDNA have not so far been explored in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data indicate that circulating SEPT9 DNA as a methylation marker is as sensitive as 87% in detecting stage I CRC, 84% in detecting stage II CRC, and 90% in overall CRC [68]. Two recent studies have shown that tumor-specific methylation changes can be detected in plasma two years before tumor diagnosis [69,70]. Further research by Guo et al showed that ctDNA methylation changes in plasma could not only be applied in the screening of tumors but also reveal the tissue source of tumors [71].…”
Section: Clinical Application Of Ctcs and Ctdna In Crcmentioning
confidence: 99%
“…These techniques have impacted every field of molecular research, escalating previously used sequencing technologies [ 11 ], and opening the way to the -omic sciences foundation [ 1 , 2 ]. Indeed, NGS methods allow the sequencing of entire genomes [ 12 , 13 , 14 , 15 ], of exomes [ 16 , 17 , 18 ], of panels of genes related to a disease of interest [ 19 , 20 , 21 ], or of a single gene [ 22 , 23 , 24 , 25 , 26 ], but can also be used to explore the entire transcriptome [ 27 , 28 , 29 ], small RNAs [ 30 , 31 , 32 ], the epigenome [ 33 , 34 ], and the microbiome [ 35 , 36 , 37 , 38 ].…”
Section: High-throughput Analysesmentioning
confidence: 99%
“…In addition to the study of sequence variations at the DNA level, NGS methods can be used to study genetic variability, and the mechanisms underlying the onset of specific diseases at epigenetic, transcriptomic and metagenomic levels [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Indeed, several factors, other than individual genetic predisposition, such as diet, environmental factors and lifestyle, can influence the epigenome, the transcriptome and the microbiome [ 2 , 50 ].…”
Section: High-throughput Analysesmentioning
confidence: 99%
See 1 more Smart Citation